2012
DOI: 10.1021/ac203200x
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interlaboratory Reproducibility of Ultra Performance Liquid Chromatography–Time-of-Flight Mass Spectrometry for Urinary Metabolic Profiling

Abstract: Liquid chromatography coupled to mass spectrometry (LC-MS) is a major platform in metabolic profiling but has not yet been comprehensively assessed as to its repeatability and reproducibility across multiple spectrometers and laboratories. Here we report results of a large interlaboratory reproducibility study of ultra performance (UP) LC-MS of human urine. A total of 14 stable isotope labeled standard compounds were spiked into a pooled human urine sample, which was subject to a 2- to 16-fold dilution series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…In general, studies gauging the benefit of high-versus low-resolution systems are scarce in the field. Some ring trials have been conducted, comparing different laboratories with different mass spectrometers, chromatographic systems, data analysis pipelines, etc., with the aim to validate the hypothesis-generating power of metabolomics as a whole [34,35]. However, those have too many interfering factors to be able to attribute differences found to the resolution of the mass spectrometer used.…”
Section: Introductionmentioning
confidence: 99%
“…In general, studies gauging the benefit of high-versus low-resolution systems are scarce in the field. Some ring trials have been conducted, comparing different laboratories with different mass spectrometers, chromatographic systems, data analysis pipelines, etc., with the aim to validate the hypothesis-generating power of metabolomics as a whole [34,35]. However, those have too many interfering factors to be able to attribute differences found to the resolution of the mass spectrometer used.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolome refers to all metabolites present in a given biological system [2]. Metabolomics is an “omics” technology that allows metabolome characterization [3, 4]. Metabolomics is particularly interesting in exploring IEM given their intrinsic with metabolism [5].…”
Section: Introductionmentioning
confidence: 99%
“…Such heterogeneity can thus result in discrepancies in the results produced from different places and prevent their generalisation. Several inter-laboratory studies have attempted to validate the accuracy of the metabolomics approach, but these studies all used similar instruments, either NMR of different magnetic fields (Viant et al 2009 ; Ward et al 2010 ) or GC–MS (Allwood et al 2009 ) and LC–MS (Benton et al 2012 ) of the same type. When using tight standardized conditions among the partners these studies showed a high degree of inter-laboratory repeatability.…”
Section: Introductionmentioning
confidence: 99%